2021
DOI: 10.1088/1741-4326/abda00
|View full text |Cite
|
Sign up to set email alerts
|

Multiple-isotope pellet cycles captured by turbulent transport modelling in the JET tokamak

Abstract: For the first time the pellet cycle of a multiple-isotope plasma is successfully reproduced with reduced turbulent transport modelling, within an integrated simulation framework. Future nuclear fusion reactors are likely to be fuelled by cryogenic pellet injection, due to higher penetration and faster response times. Accurate pellet cycle modelling is crucial to assess fuelling efficiency and burn control. In recent JET tokamak experiments, deuterium pellets with reactorrelevant deposition characteristics were… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 42 publications
1
15
1
Order By: Relevance
“…Control of the plasma H:D isotope mix using solely shallow pellets (in H or D) was demonstrated in recent experiments, attaining 50%/50% H/D ratio [61]. The isotope mix propagates to the core on the energy confinement timescale, in agreement with quasilinear theory as reported in [62] where it is shown that the combination of stabilisation by R/L n and destabilisation by R/L T leads to ITG drive and thus to fast isotope mixing following each pellet injection throughout the pellet train. Analysis of the dataset for different pellet sizes, content and plasma current, and including for the first time pellets with ITER-like ablation and relative pellet size, indicate high efficiency for pellets with ablation depth r/a < 0.95, but falling sharply for shallower pellets.…”
Section: Core and Pedestal Transport And Confinementsupporting
confidence: 77%
“…Control of the plasma H:D isotope mix using solely shallow pellets (in H or D) was demonstrated in recent experiments, attaining 50%/50% H/D ratio [61]. The isotope mix propagates to the core on the energy confinement timescale, in agreement with quasilinear theory as reported in [62] where it is shown that the combination of stabilisation by R/L n and destabilisation by R/L T leads to ITG drive and thus to fast isotope mixing following each pellet injection throughout the pellet train. Analysis of the dataset for different pellet sizes, content and plasma current, and including for the first time pellets with ITER-like ablation and relative pellet size, indicate high efficiency for pellets with ablation depth r/a < 0.95, but falling sharply for shallower pellets.…”
Section: Core and Pedestal Transport And Confinementsupporting
confidence: 77%
“…A wide overview on the progress in understanding core transport in tokamaks is presented in [26], including examples of the validation of QL models against present experiments. Some recent TGLF validation carried out for DIII-D and AUG plasma discharges is reported in [27][28][29][30], while recent QLK validation works are presented in [24,[31][32][33][34] for hybrid, baseline, and mixedisotope JET experiments. Bearing in mind that DTT will operate in a T e > T i regime, a particularly relevant validation work is that presented in [35], with results on both TGLF and QLK modelling of an extensive set of experimental results from AUG and JET-ILW in regimes with high T e /T i .…”
Section: General Settingsmentioning
confidence: 99%
“…Marin investigated the fast isotope mixing observed in JET, where the central neutron rate was found to quickly increase just after the injection of a deuterium pellet in a pure hydrogen plasma [16]. To model this phenomenon, they performed integrated modeling using JINTRAC with Qua-LiKiz and HPI2 as physics-based turbulent transport and pellet models, respectively [17]. They successfully reproduced the fast penetration of deuterium to the core.…”
Section: B Isotope Effects In Particle Transportmentioning
confidence: 99%